Improving of agricultural real estate market of Ukraine based on international experience - Martyn, A.; Avramchuk, B. (Land Management, Cadastre and Land Monitoring, 2017)
Since independence the great land reform had been held that brought private property in land relations in Ukraine. But at the same time the agricultural land market through the introduction of a moratorium on the sale of agricultural land had stopped functioning. The lack of a common classification of property for agricultural purposes, a number of legal and legislative aspects are currently the main obstacles to the creation of a transparent market for agricultural real estate, which includes not only the land but also buildings and structures that are directly or not used in agriculture . The main aim of the article is to highlight the constructive action to improve the functioning of the market for agricultural real estate, namely the possibility of creating an integrated classifier to agricultural real estate and amend the information files of the State Land Cadastre and State Register of rights to real estate. The successful operation of agricultural property market in Ukraine would be ruling out in the absence of a common classification of real estate for agricultural purposes, so this classification should be offered. At this stage, the existing categories of land use purpose designed classifier property for agricultural purposes is integrated with links to existing Classification and aims to unify all objects of agricultural purpose in a single classification. Creation classification of objects of agricultural purpose, of course, accelerate the successful start functioning agricultural estate market, but it in no time, not provide it completely. And one of the main obstacles to implementing it is valid to do at this time in Ukraine a moratorium on the sale of agricultural land. According to the authors, the lack of legitimate opportunities to operate in the market for agricultural real estate leads to illegal activities to the ground and holding back the development of the State Land Cadastre and slows conduct any research and development in the field of land evaluation. The necessary preconditions for the introduction of the land market should be: - Completion of the establishment of the land cadastre, which will set clear boundaries of land and their legal owners all over Ukraine; - Develop a reasonable methodology for determining the minimum price of land because of its fertility, location and other characteristics of each region of Ukraine. The article also proposed a few changes to the information file about the registered property rights to land and on registered land. In addition, these changes are based on the capabilities of monitoring land market and summarize data on the prices of land by Design State Committee for Land Resources of Ukraine on the land market monitoring and summarizing data on land prices. Keywords: land cadastre, real estate, agri-food sphere, land parcel, agricultural real estate market.